Free Radical Scavenging and Analgesic Activities of 70% Ethanol Extract of Luvunga sarmentosa (BI.) Kurz from Central Kalimantan - Utami Islamiati; Hanifah Khairun Nisa; Hilkatul Ilmi; Lidya Tumewu; Myrna Adianti; Tutik Sri Wahyuni; Aty Widyawaruyanti; Achmad Fuad Hafid (Borneo Journal of Pharmacy, 2022)
Luvunga sarmentosa, commonly known as saluang belum, is widely used in Kalimantan to relieve pains, rheumatism, boost the immune system, and fever. The research on the free radical scavenging and analgesic effect of the L. sarmentosa stem extract has not been reported. This study aimed to evaluate the free radical scavenging and analgesic activity of the ethanol extract of L. sarmentosa. The L. sarmentosa stem was extracted using 70% ethanol and tested for free radical scavenging using the 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) and analgesic activity, acetic acid-induced writhing test, and hot plate test in an animal model. The results showed that the 70% ethanol extract of the L. sarmentosa had an anti-free radical scavenging and analgesic activity. The extract has weak free radical scavenging with an IC50 value of 293.45 µg/mL. Analgesic activity using the writhing test indicated that the extract significantly reduced the writhes count after oral administration in a dose-dependent manner compared to the negative control. Extract at a dose of 550 mg/kg BW can reduce the writhing test by 67.60% compared to others. In contrast, the diclofenac sodium reduced the number of writhes by 74.74%. While in a hot plate, the extract at a dose of 550 mg/kg BW produced a maximum possible analgesia (MPA) of 17.64%, lower than the MPA of diclofenac sodium (51.01%). Analgesic activity of the extract has higher inhibition on the writhing test than on the hot plate. The extract could be responsible for the peripheral mechanism by inhibiting the prostaglandin biosynthesis.